(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Electrical energy is very imperative for ever day life and a spine for the industry. Electricity is indiscipline to our daily life with increasing need of electricity the power theft is also increasing power theft is a problem that continues to plague power sector across the whole country the objective of this project is to design a system in order to avoid the displeasure for the users from the fty bill irrespective of the use of the electricity due to theft using GSM module